2016
DOI: 10.14739/2409-2932.2016.1.62036
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful search and characteristic of anti-inflammatory activity of sodium (3-R-2-оxo-2Н-[1,2,4]triazino[2,3-c]quinazolin-6-yl)alkylcarboxylates and their halogen containing analogues

Abstract: Експериментальна та клінічна фармакологія Experimental and clinical pharmacology 60 Н аявність у сучасних нестероїдних протизапаль-них засобів (НПЗЗ) низки серйозних побічних реакцій (гастро-, нефро-та гепатотоксичність та ін.) спонукає до пошуку нових молекул із протизапальною дією, що придатні для створення на їхній основі більш ефективних і безпечних лікарських засобів із вказаною дією [1]. У зв'язку з цим привертають увагу маловідомі натрій (3-R-2-оксо-2Н- [1,2,4] У роботі розроблені підходи щодо створення… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Thus, the activity of these compounds exceeded the pharmacological effect of the reference-compound «Diclofenac» by 33.1%, 10,8%, 32.0% and 28.1%, correspondingly. The SAR-analysis showed that a high anti-inflammatory activity was observed for pyrrolo[1,2-a][1,2,4]triazino [2,3-c]quinazoline derivatives (compounds 3a-j) which can be explained by their structural similarity to the known anti-inflammatory agents [4][5][6]. At the same time, the compound 2a as well as substituted pyrrolo [1,2-a 10.0…”
Section: Anti-inflammatory Activity Of the Synthesized Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the activity of these compounds exceeded the pharmacological effect of the reference-compound «Diclofenac» by 33.1%, 10,8%, 32.0% and 28.1%, correspondingly. The SAR-analysis showed that a high anti-inflammatory activity was observed for pyrrolo[1,2-a][1,2,4]triazino [2,3-c]quinazoline derivatives (compounds 3a-j) which can be explained by their structural similarity to the known anti-inflammatory agents [4][5][6]. At the same time, the compound 2a as well as substituted pyrrolo [1,2-a 10.0…”
Section: Anti-inflammatory Activity Of the Synthesized Compoundsmentioning
confidence: 99%
“…61-70 strategy. Our previous studies showed the prospects of search for anti-inflammatory agents among condensed [5] and spiro-condensed [7] quinazoline derivatives.…”
Section: Introductionmentioning
confidence: 99%